Effect of Underlying Renal Disease on Nutritional and Metabolic Profile of Older Adults with Reduced Renal Function - Lai, Silvia; Amabile, Maria Ida; Altieri, Silvia; Mastroluca, Daniela; Lai, Carlo; Aceto, Paola; Crudo, Massimiliano; D’Angelo, Anna Rita; Muscaritoli, Maurizio; Molfino, Alessio (Frontiers in Nutrition, 2017)
BACKGROUND: Chronic kidney disease (CKD) is a common condition in the general population, particularly among older adults. Renal impairment is in turn associated with metabolic and nutritional derangements and to increased risk of cardiovascular disease (CVD). AIM: To compare the metabolic, nutritional and cardiovascular impact of reduced kidney function between patients with and without known renal disease. MATERIALS AND METHODS: We enrolled 76 Patients (age ≥ 65 years) with reduced renal function were divided into two groups: Group A, with history of renal disease, and Group B with unknown renal disease. Metabolic and nutritional parameters, including involuntary body weight loss (BWL) in the previous six months, mineral metabolism, inflammatory indices and left ventricular mass index (LVMI) were evaluated. RESULTS: A total of 76 patients were enrolled. Group A (n=39, M:24, F:15) showed greater BWL with a significant reduction of vitamin D3, transferrin, cholinesterase, serum iron, hemoglobin and LVMI. Conversely, Group B (n=37, M:23, F:14) showed significantly increased, intact parathyroid hormone, total cholesterol, LDL, triglycerides and C-reactive protein when compared to group A. CONCLUSION: Reduced renal function is common among older adults, and the positive history of renal disease may negatively impact on several metabolic and nutritional parameters related to increased cardiovascular risk.